2018
DOI: 10.1021/acs.energyfuels.8b01198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction between Sodium and Oxides of Silicon and Aluminum on the Formation of Fine Particulates during Synthetic Char Combustion

Abstract: Alkali and alkaline earth metals (AAEM), especially sodium, make a great contribution to the formation of fine particulates during coal combustion. Extraction and loading through chemical methods have been widely used for coal pretreatment to change the occurrence and content of sodium but could not load intrinsic minerals. In this study, synthetic char was used as a mineral carrier to study the characteristic of fine particulate formation during coal combustion. The silica and alumina were added to synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It can be seen from Figure a that the ultrafine particles produced by the de-alkali coal are irregular and do not contain crystals. However, there are crystals that significantly formed in the ultrafine particles of the de-alkali coal with Na salts added, which is also reported in ref . Among them, the ultrafine particles of the coal with NaCl added had the highest crystal content, followed by coal with Na 2 SO 4 and NaAc added.…”
Section: Resultssupporting
confidence: 70%
“…It can be seen from Figure a that the ultrafine particles produced by the de-alkali coal are irregular and do not contain crystals. However, there are crystals that significantly formed in the ultrafine particles of the de-alkali coal with Na salts added, which is also reported in ref . Among them, the ultrafine particles of the coal with NaCl added had the highest crystal content, followed by coal with Na 2 SO 4 and NaAc added.…”
Section: Resultssupporting
confidence: 70%
“…Increased Na in ultrafine PM is supposed to be mainly Na 2 SO 4 . Cl has been found to promote Na to participate in sub-micrometer PM . Therefore, the sulfurization of Na could also stabilize the Na species, mitigating the Na capture by Si–Al-dominating particles.…”
Section: Resultsmentioning
confidence: 99%
“…Na has been considered one of the important resources of ultrafine particles from combustion of Zhundong lignite. Its transformation in an early stage of lignite combustion , and interactions with other major minerals , have been widely investigated. However, recent studies found that Mg, Ca, Fe, and S could not be neglected because they may be abundant in fine PM produced from lignite combustion. , Besides, a considerable proportion of Ca and Mg has also been found as ion-exchangeable forms in lignite, such as Victorian brown coal and Zhundong lignite. , They are easy to release during combustion and could contribute more to sub-micrometer PM.…”
Section: Introductionmentioning
confidence: 99%
“…shows that the amounts of water-soluble, ion-exchangeable, acid-soluble, and acid-insoluble Na transferred into PM 10 were 52.1, 19.4, 2.4, and 0.2 µg/g_coal, respectively. This was due to the combined effect of two factors, namely: firstly, the content of Na in the four forms of minerals correspondingly decreased ( Figure 2); secondly, the gasification ability of water-soluble Na (NaCl) was stronger than that of ion-exchangeable Na [26], and the gasification ability of acid-soluble and acid-insoluble Na was inhibited by aluminosilicate and SiO 2 [25]. Figure 8a shows that the contributions of the water-soluble, ion-exchangeable, acid-soluble, and acid-insoluble Fe to PM10 were 2.4%, 37.9%, 33.7%, and 26.0%, respectively.…”
Section: Effect Of Different From Minerals On Element Composition Andmentioning
confidence: 99%
“…The transformation process and results of minerals in different occurrence forms to different mode PM showed significant differences [19][20][21][22]. Water-soluble Na and K, such as their chlorides, are easy to vaporize, and are therefore enriched in ultrafine-mode PM [23,24], while acid-insoluble Na and K, such as Na and K in composite aluminosilicate, can exist stably at high temperatures and mainly become part of coarse-mode particles [25]. Ion-exchangeable Mg, Ca, and Fe are bound to a carbon matrix by chemical bonds, and are easily decomposed and released during combustion [26], thereby significantly contributing to all three modes of PM [21].…”
Section: Introductionmentioning
confidence: 99%